Lordosis in humans: women's accurate perceptions of men's context-dependent preferences. (April 2023) - Ranson, Jessica; Read, Orion; Semchenko, Ayten Yesim; Senveli, Zeynep; Forrest, Mitchell R.L.; Flores, Jonathon; Fiala, Vojtěch; Al-Shawaf, Laith; Lewis, David M.G.
Abstract: Semchenko and colleagues (in press) recently disentangled two evolutionary hypotheses and demonstrated that heterosexual men have mate preferences for both the morphological cue of women's lumbar curvature and the behavioral cue of back arching: Men are attracted to an intermediate degree of lumbar curvature in both short-term and long-term mating contexts, and, independent of this preference, are attracted to lordosis behavior in short-term, but not long-term, mating contexts. No research to date has investigated whether women are aware of these preferences. There are a priori reasons to expect this to be the case: An awareness of these preferences could functionally guide both appearance-enhancement and intrasexual competition strategies. Here, we tested whether women have accurate perceptions of men's preferences in the lumbar region. Across two studies ( N s = 177, 293), we found that women's perceptions align precisely with men's preferences: Women perceive men to be attracted to cues to lordosis behavior in short-term but not long-term contexts, and to be attracted to an intermediate angle of lumbar curvature independent of mating context. We hope these findings, which document previously unknown features of women's mating psychology, inspire investigations into how women might adaptively use their accurate perceptions of men's mate preferences. Highlights: We tested whether women accurately perceive men's mate preferences. Women accurately perceived men's preference for lumbar curvature. Women accurately perceived men's context-dependent attraction to lordosis behavior.